ITS barcoding using high resolution melting analysis of Cannabis sativa drug seizures in Chile: A forensic application. (November 2020) - Solano, Jaime; Anabalón, Leonardo; Figueroa, Alejandra; Gangitano, David
Highlights: A low cost and fast option with forensic applications is to use the ITS barcode with High Resolution Melting. Bar-HRM using ITS allowed to determine the genetic composition of cannabis drugs seizures in 10 cases studied. The derivative of melting, the curve shape and Tm peak, allows to distinguish the biogeographic origin in cannabis seizures. The derivative of melting, the curve shape, and the Tm peak, allows to determine genetic composition of cannabis. Clonally propagated in cannabis can be confirmed by ITS region with HRM analysis. Abstract: Cannabis sativa L. is a plant cultivated worldwide as a source of fiber, medicine, and intoxicant. Traditionally, C. sativa is divided into two main types: fiber type (hemp) and drug type. Drug-type C. sativa differs from hemp by the presence of a high quantity of the psychoactive drug, Δ 9 -tetrahydrocannabinol (Δ 9 THC). Cannabis sativa is the most commonly used used illicit controlled substance in Chile. Chile is the third greatest consumer of Cannabis in South America. The objective of this study was to determine the genetic composition of ten drug seizures of Cannabis spp . in the south of Chile using a high resolution melting (HRM) strategy combined with a barcoding marker, ITS. C. sativa samples were selected from previously processed more than a thousand crime cases at the, Araucania region crime lab, National Dept. of Health. Ten cases were selected. Sample collection was based on the following: a) dry and fresh samples with no evidence of decomposition or degradation, b) defined plant fragments such as flowers and leaves from individual plants and, c) samples with different content of THC, CBN and CBD. Five sub samples were randomly selected from each case (N = 50). The commercial Silver Haze strain was used as a control. Two real-time PCR and HRM analyses were conducted. The first analysis was performed with a representative sample of each of the 10 cases studied. Then a second assay was performed with all subsamples of cases 1, 5 and 8. Results showed that real-time PCR combined with HRM analysis using ITS allowed to determine the genetic composition of cannabis in all cases studied. The derivative of melting and the analysis of the shape of the curve and the peak of Tm, showed that three groups can be clearly distinguished. A first group exhibited a peak of Tm close to 87.4 °C and includes cases 7 and 8. A second group had a peak of Tm close to 87.6 °C and includes case 5. A third group displayed a peak of Tm close to 87.9 °C and includes case 1, 6 and Silver Haze strain. A second experiment was performed using subsamples of cases 1, 5 and 8. Case 1 displayed a unique composition of the drug suggesting that this seizure contained cannabis clonally propagated. In case 5, two genotypes were present, therefore this could be associated with two strain or two different origin. Case 8, was composed of a mixture of cannabis strains indicating the presence of various crop type and/or different biogeographic origin. In general, our results suggested genetically homogeneous seizures from Araucanía Region. The high latitude (37° 35′ and 39° 37′ South latitude) and the natural geographic borders that surround southern Chile helps the control of cannabis traffic into the country. Finally, HRM analysis coupled with the barcode ITS demonstrated to be a rapid and low-cost screening method.